2019
DOI: 10.1017/s0950268818003187
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude, distribution, risk factors and care-seeking behaviour of acute, self-reported gastrointestinal illness among US Army Soldiers: 2015

Abstract: Throughout history, acute gastrointestinal illness (AGI) has been a significant cause of morbidity and mortality among US service members. We estimated the magnitude, distribution, risk factors and care seeking behaviour of AGI among the active duty US Army service members using a web-based survey. The survey asked about sociodemographic characteristics, dining and food procurement history and any experience of diarrhoea in the past 30 days. If respondents reported diarrhoea, additional questions about concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…These findings support other work that has found that a long duration of illness [5,11], concurrent fever [2,5,15], longer diarrhea duration [2], and vomiting [2,16] were significantly associated with care seeking behavior in multivariable analyses. Other work has additionally shown other concurrent symptoms, including headaches [11] and abdominal cramps [15] to be associated with healthcare-seeking behavior, but these variables were not assessed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…These findings support other work that has found that a long duration of illness [5,11], concurrent fever [2,5,15], longer diarrhea duration [2], and vomiting [2,16] were significantly associated with care seeking behavior in multivariable analyses. Other work has additionally shown other concurrent symptoms, including headaches [11] and abdominal cramps [15] to be associated with healthcare-seeking behavior, but these variables were not assessed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Primarily, National Health Interview Survey (NHIS) data showed that gastrointestinal illness was associated with income, with a negative correlation between income and overall health, including AGI [ 35 , 36 ]. This may be due to the different lifestyle behaviors in this group, such as health habits, patterns of dining out, and awareness of hygienic conditions [ 37 , 38 ]. Moreover, intestinal microorganisms may have a prominent effect on disease [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMs are at increased risk of developing AD due to their deployments to overseas locations [15], and exacerbated by the fact that a number of those locations have concerning levels of AMR in relevant pathogens [9][10][11][12]. Episodes of diarrheal disease can have detrimental impact on troop readiness and mission operations, underscoring the importance of timely resolution of symptoms in this population [16][17][18][19]. It is therefore essential for military medical providers to understand the current trends in resistance profiles of enteropathogens in SMs to inform proper, timely treatment options.…”
Section: Introductionmentioning
confidence: 99%